Ocular Signs of Chiari Malformation - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
Twenty-eight patients (14 females and 14 males aged between four and 34 years) with myelomeningocele and Chiari malformations were examined neuro-ophthalmologically at the Karolinska Institute, Huddinge University Hospital, Huddinge, Sweden.